2013
DOI: 10.1074/jbc.m112.442491
|View full text |Cite
|
Sign up to set email alerts
|

The Soluble Form of LR11 Protein Is a Regulator of Hypoxia-induced, Urokinase-type Plasminogen Activator Receptor (uPAR)-mediated Adhesion of Immature Hematological Cells

Abstract: Background: Serum levels of the soluble LR11 fragment (sLR11) increase in patients with acute leukemia. Results: Hypoxia-induced factor (HIF)-1␣ activation increases LR11 levels, and sLR11 enhances adhesion of HSPCs to BM stromal cells via a uPAR-mediated pathway. Conclusion: sLR11 regulates hypoxia-induced attachment of HSPCs. Significance: sLR11 may stabilize the hematological pool size by controlling HSPC attachment to the BM niche.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 55 publications
0
20
1
Order By: Relevance
“…Previous studies also suggest that it is the mature form of sorLA that is fully functional, and interestingly, the extracellular shedding of sorLA only occurs when sorLA interacts with TACE (TNFα Converting Enzyme) at the cell surface (16,19). The role of sorLA shedding remains largely elusive, however, the shed ectodomain appears to influence signaling pathways and to regulate cell adhesion (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also suggest that it is the mature form of sorLA that is fully functional, and interestingly, the extracellular shedding of sorLA only occurs when sorLA interacts with TACE (TNFα Converting Enzyme) at the cell surface (16,19). The role of sorLA shedding remains largely elusive, however, the shed ectodomain appears to influence signaling pathways and to regulate cell adhesion (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…18 We previously reported that HIF-1α binds to the proximal 144-bp LR11 promoter in a region where a potential HIF-1-binding site can be induced by hypoxia. 19 The present study found that HIF-1α knockdown decreased LR11 expression under hypoxia, indicating that HIF-1α plays a key role in LR11 expression under such conditions.…”
Section: Lr11 Deletion Prevents Pulmonary Vascular Remodeling Via Hifmentioning
confidence: 68%
“…Although we found that sLR11 alone induced the proliferation of cultured PASMC, endothelial cells and immature cells such as hematopoietic stem and progenitor cells might also regulate serum sLR11 levels in pulmonary hypertension. 19,26 We previously showed that sLR11 could be a useful biomarker of conditions such as atherosclerosis, 17 large B-cell lymphoma, 27 non-Hodgkin lymphoma, 28 follicular lymphoma, 29 diabetic retinopathy, 30 and acute coronary syndrome. 31 Overall, sLR11 might serve as a potentially noninvasive and objective parameter of responses to therapy, although further investigation using other models of PH is essential to define how much circulating sLR11 levels reflect the pathological conditions of PASMC in patients.…”
Section: Cd38mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia could disrupt tissue integrity through repression of E-cadherin expression (Fu et al, 2014). Hypoxia could also promote proteolytic activity at the invasive front and alter the interactions between integrins and components of the extracellular matrix (Nishii et al, 2013). The high HIFPH3 expression in NSCLC could facilitate metastasis by regulating HIF-1α, resulting in hypoxia responses in tumor.…”
Section: Discussionmentioning
confidence: 99%